Administration of L-arginine plus L-citrulline or L-citrulline alone successfully retarded endothelial senescence. - Tomoe Tsuboi; Morihiko Maeda; Toshio Hayashi (PLoS ONE, 2018)
L-citrulline and L-arginine supplementation has been shown to have several beneficial effects on the cardiovascular system. Nitric oxide (NO) protects against the progression of atherosclerosis and is synthesized by nitric oxide synthase (NOS), which converts L-arginine (L-Arg) into L-citrulline (L-Cit). Our previous study revealed that chronic administration of a combination of L-Cit and L- Arg has a better therapeutic effect on high cholesterol-induced atherosclerosis in rabbits. We investigated how L-Arg and L-Cit affect endothelial function, aging and atherosclerosis. Following a 3-day stimulation of human umbilical venous endothelial cells (HUVECs) with high glucose (HG: 22 mM) and L-Arg (300 μM), L-Cit (300 μM) or L-Arg plus L-Cit (LALC: each 150 μM) supplementation, endothelial senescence and function were evaluated. These amino acids were also administered to dyslipidemic type 2 diabetic (ZDFM) rats fed a high cholesterol diet. They were fed L-Arg or L-Cit or LALC for four weeks. Aortic senescence was investigated by measuring senescence-associated ß-galactosidase (SA-ß-gal), telomerase activity, DNA damage and p16INK4a protein expression. Only L-Cit and LALC supplementation retarded the HG-induced endothelial senescence, as evaluated by SA-ß-gal activity, a widely used marker of cellular senescence, p16INK4a expression, a senescence-related protein, and DNA damage. Under HG conditions, L-Cit and LCLA restored telomerase activity to levels observed under normal glucose (NG) conditions. Under HG conditions, L-Cit decreased ROS production, as measured by CM-H2DCFDA and the expression of p67phox, a major component of NADPH oxidase. Under HG conditions, L-Cit and LALC increased NO production, as measured by DAF-2AM. Endothelial NO synthase (eNOS) and phosphorylated eNOS were decreased under HG conditions and L-Cit and LALC significantly increased these levels. Arginase 2 protein expression increased under the HG conditions, and L-Cit and LALC significantly attenuated this effect. In ZDFM rats, SA-ß-gal activity was detected on the aortic endothelial surface; however, L-Cit and LALC reduced these levels. L-Cit and LALC both decreased the proportion of senescent cells. Furthermore, treatment with LALC for 4 weeks increased plasma NO production. Therefore conclusively, L-citrulline supplementation rescued NO levels better than L-arginine supplementation by inhibiting ROS production and arginase 2 protein expression. Consequently, L-Cit and LCLA supplementation retaeded HG-induced endothelial senescence.